Patterns of biopsy-proven kidney disease amongst South African adults from 1995 to 2017 - Esmail, Ahmed Mushtak; Bates, William D; Amirali, Mazhar Hussein; Jardine, Thabiet; Davids, Mogamat Razeen (African Journal of Nephrology, 2023)
Introduction: Little data is available on biopsy-proven kidney disease in African countries. In this study, we have described the patterns of biopsy-proven kidney disease amongst South African adults encountered over a 23-year period and report whether these have changed over time. Methods: This retrospective study included all adults who underwent a native kidney biopsy at Tygerberg Hospital in Cape Town from January 1995 to December 2017. Only the first biopsy for each patient was included in the analysis. From patient records, we extracted demographic and clinical information and details of the kidney biopsies, including the indications and the final histopathological diagnosis. Results: During the study period, 2227 first native kidney biopsies were performed. The median age of the patients was 38.0 years (interquartile range 30.0–48.1 years), and 53.3% were female. The most common indication for biopsy was nephrotic syndrome (38.6%). Glomerulonephritis (GN) was the most common pattern of kidney disease, with similar numbers of cases of primary and secondary glomerular disease. Among the primary glomerular diseases, mesangiocapillary GN (34.5%) was the most common, followed by focal segmental glomerulosclerosis (22.3%) and membranous nephropathy (15.8%). Among the secondary glomerular diseases, lupus nephritis was the most common (39.1%), followed by human immunodeficiency virus-associated nephropathy (HIVAN, 22.1%), and diabetic nephropathy (14.4%). IgA nephropathy was uncommon, accounting for only 2.0% of all glomerular disease, as was hypertensive kidney disease, which was diagnosed in only 1.3% of all our biopsies. Conclusions: Over the last two decades, mesangiocapillary GN was the most common primary glomerular disease and lupus nephritis the most common secondary glomerular disease. There was a steady increase in the number of patients with HIVAN. Hypertensive nephropathy was an uncommon histological diagnosis, and IgA nephropathy remains rare.